The Maia detector array and x-ray fluorescence imaging system: Locating rare precious metal phases in complex samples - Ryan, Chris; Siddons, D.; Kirkham, R.; Li, Z.; De Jonge, M.; Paterson, D.; Cleverley, J.; Kuczewski, A.; Dunn, P.; Jensen, M.; De Geronimo, G.; Howard, D.; et al. (SPIE, 2013)
X-ray fluorescence images acquired using the Maia large solid-angle detector array and integrated real-time processor on the X-ray Fluorescence Microscopy (XFM) beamline at the Australian Synchrotron capture fine detail in complex natural samples with images beyond 100M pixels. Quantitative methods permit real-time display of deconvoluted element images and for the acquisition of large area XFM images and 3D datasets for fluorescence tomography and chemical state (XANES) imaging. This paper outlines the Maia system and analytical methods and describes the use of the large detector array, with a wide range of X-ray take-off angles, to provide sensitivity to the depth of features, which is used to provide an imaging depth contrast and to determine the depth of rare precious metal particles in complex geological samples. © 2013 SPIE.